2016
DOI: 10.1007/s12262-016-1543-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in Surgically Treated Carcinoma Penis Patients and Their Partners

Abstract: Most common treatment offered to carcinoma penis patients is surgery. This results in not only mutilation of the genitals but also affects their sexuality. The treating physician fails to address the issue due to the paucity of the data in this regard. Hence, we decided to evaluate sexuality in these patients after surgical treatment for penile cancer. Most of the times, their partners also face problems of sex and sexuality, regarding which there is no literature. Hence, we decided to include their partners a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Of the 1725 retrieved from the search, 1662 articles were excluded following the application of the inclusion and exclusion criteria during the title and abstract screening, see Figure 1. In total, 62 fulltext publications were reviewed in full and 45 were excluded with reasons and 18 articles were included, reporting the results from 17 studies in the final review (Kieffer et al, 2014, Sosnowski et al, 2016, Wan et al, 2018, Windahl et al, 2004, Witty et al, 2013, Mortensen and Jakobsen, 2013, Skeppner and Fugl-Meyer, 2015, Skeppner et al, 2008, Opjordsmoen et al, 1994, Bhat et al, 2018, Bullen et al, 2010, Drager et al, 2017, Ficarra et al, 2000, Gordon et al, 2017, Bullen et al, 2009, D'Ancona et al, 1997, Bullen et al, 2010, Bullen et al, 2009.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 1725 retrieved from the search, 1662 articles were excluded following the application of the inclusion and exclusion criteria during the title and abstract screening, see Figure 1. In total, 62 fulltext publications were reviewed in full and 45 were excluded with reasons and 18 articles were included, reporting the results from 17 studies in the final review (Kieffer et al, 2014, Sosnowski et al, 2016, Wan et al, 2018, Windahl et al, 2004, Witty et al, 2013, Mortensen and Jakobsen, 2013, Skeppner and Fugl-Meyer, 2015, Skeppner et al, 2008, Opjordsmoen et al, 1994, Bhat et al, 2018, Bullen et al, 2010, Drager et al, 2017, Ficarra et al, 2000, Gordon et al, 2017, Bullen et al, 2009, D'Ancona et al, 1997, Bullen et al, 2010, Bullen et al, 2009.…”
Section: Search Resultsmentioning
confidence: 99%
“…The devastating impact that a new diagnosis of penile cancer and related treatments was identified as a clinically significant theme across many of the studies related to unmet intimacy needs. Several studies identified that participants reported that their relationship with their partners was affected by sexual dissatisfaction (Bhat et al, 2018, Ficarra et al, 2000, Skeppner and Fugl-Meyer, 2015, Skeppner et al, 2008, Sosnowski et al, 2016, Wan et al, 2018. Moreover, in one study, 90% of the participants experienced anxiety in relation to their sexual performance (Bhat et al, 2018).…”
Section: Interpersonal/intimacy Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, the patients who underwent total penectomy reported higher levels of sexual desire but less sexual satisfaction than their partial penectomy counterparts which affected the relationship with their partners. The authors reported an absolute overall reduction in sexual satisfaction among those treated with partial penectomy (35). The outcomes were poorer still in those treated with total penectomy.…”
Section: Partial Penectomymentioning
confidence: 95%
“…Bhat et al described twelve patients, two had undergone total penectomy and ten underwent partial penectomy (35). The partial penectomy cohort had intact masculine selfimage prior to treatment that was lost in all ten patients postoperatively.…”
Section: Partial Penectomymentioning
confidence: 99%